SMART PRESENSI MENGGUNAKAN QR CODE DENGAN SECURE HASH ALGORITHM 2 (SHA-2) - Wijaya, Ivan; Herwindiati, Dyah Erny; Hendryli, Janson (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
This research was motivated by problems during the process of attendance at the Mid-Semester Examination (UTS) and Final Semester Examination (UAS). The problem begins when the student attendance process is still manual and not online or connected to the database. This study aims to determine the online student attendance system so that exam supervisors no longer give signatures on student exam cards so that the exam runs well and efficiently. The data that will be used are student data taken when the administrator fills in the student detail data. The system design made is by using a QR Code Scanner and data encryption using the SHA 512 method. Using this application system includes the QR Code Scanning process, inserting a QR Code into the student exam card. Then the smart phone application is used as a QR Code scanner. The test used to give a test the feasibility of the system in this study is to use system error level testing, black box testing and the presence of QR Code testing in certain cases. In the testing that has been done, it can be concluded that the Smart Presensi application can make it easier to do attendance and student attendance data recapitulation because the system application is directly connected to the database.